Tales from Shakespeare - Charles Lamb and Mary Lamb (London Reading Publishers, 2016)
In 1807, Charles Lamb and his sister Mary wrote a collection of stories retelling twenty of Shakespeare's plays for children. Ranging from Romeo and Juliet to the delightful fancy of A Midsummer Night's Dream and the humour of As You Like it, this collection of vivid adaptations offers budding readers an accessible route to Shakespeare's works.
Keywords: Tales -- Short stories -- English drama